Penerapan Peraturan Mahkamah Agung Nomor 1 Tahun 2024 Tentang Pedoman Mengadili Perkara Pidana Berdasarkan Keadilan Restoratif Ditinjau Dari Istihsan: Studi Di Pengadilan Negeri Mentok Kelas II - Muttawadi, Ichsan; Winarno, Winarno; Anwar, Reski (JYRS: Journal of Youth Research and Studies, 2025)
Restorative justice is the resolution of criminal cases involving the perpetrator, victim, the perpetrator/victim's family, and other related parties to jointly seek a fair resolution by emphasizing restoration to the original state and not retaliation. Supreme Court Regulation Number 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice is a regulation that regulates the implementation of restorative justice in the District Court. In the implementation of PERMA Number 1 of 2024 at the Mentok District Court, there are obstacles, namely the victim does not want to take restorative justice because he feels aggrieved so that the victim hopes for retaliation and the consequences received by the perpetrator in the form of sanctions and punishments stipulated in the court decision, the perpetrator makes the same or similar mistakes within a period of 3 (three) years since the perpetrator received a permanent court decision, and has become the third stage in seeking restorative justice after the investigation stage by the police and continued at the prosecution stage by the prosecutor's office which also seeks restorative justice. associated with istihsan aims to bring the goodness of general law to laws whose application is exceptional and cannot be fulfilled due to challenges and obstacles that occur in the field